PENGELOLAAN PERSIAPAN AKREDITASI SEKOLAH DI MADRASAH ALIYAH - Basthomi, Yazid Al; Sunandar, Asep; Timan, Agus (Universitas Tanjungpura, 2024)
This study aims to gather information regarding the preparation of school administrative staff in the management of preparatory accreditation conducted at one of the Madrasah Aliyah. Based on this focus, researchers used a qualitative approach by Miles Huberman which started with data collection, data reduction, data presentation, and verification or drawing conclusions. The types of data sources in this study are divided into two, namely primary data and secondary data. For primary data sources, namely direct research objects in the form of interview notes, results of field observations, and information, all of which were obtained directly when conducting research. Whereas secondary data sources come from existing data, collected by agency investigators, previous researchers and previous organizations. Sources of data in this study are derived from observations, interviews, and documentation studies. The results of interviews with informants showed that there was still excessive workload on TAS, the madrasah's fragility was very complete, and the madrasah principal played an active role in preparing for school accreditation. The preparation for accreditation of the Madrasah Aliyah school has been quite good when viewed from the age of the madrasa which is still running for 2 years.Keywords: Management, Preparation, School Accreditation AbstrakPenelitian ini bertujuan untuk menggali informasi mengenai persiapan tenaga administrasi sekolah dalam pengelolaan persiapan akreditasi yang dilakukan di salah satu Madrasah Aliyah. Berdasarkan fokus tersebut peneliti menggunakan pendekatan kualitatif oleh Miles Huberman yang diawali dari pengumpulan data, reduksi data, penyajian data, serta verifikasi atau penarikan kesimpulan. Jenis sumber data penelitian ini terbagi menjadi dua yaitu data primer serta data sekunder. Untuk sumber data primer yaitu objek penelitian langsung berupa catatan hasil wawancara, hasil observasi lapangan, dan informasi yang semuanya diperoleh secara langsung saat melakukan penelitian. Sedangkan sumber data sekunder berasal dari data yang sudah ada, dikumpulkan oleh penyidik instansi, peneliti terdahulu serta organisasi sebelumnya. Sumber data pada penelitian ini yaitu berasal dari hasilpengamatan, wawancara, serta studi dokumentasi. Hasil wawancara dengan informan diperoleh hasil bahwa masih terdapat pembebanan kerja yang berlebihan terhadap TAS, fasilitas madrasah sudah sangat lengkap, dan kepala madrasah berperan aktif dalam persiapan akreditasi sekolah. Persiapan akreditasi sekolah di Madrasah Aliyah memiliki persiapan yang cukup baik jika dilihat dari umur madrasah yang masih berjalan 2 tahun. Kata Kunci: Manajemen, Persiapan, Akreditasi Sekolah